Educação de jovens e adultos na Universidade Federal de Minas Gerais: (re)construindo a história do Projeto de Ensino Fundamental de Jovens e Adultos – 2o Segmento – (1986-2016) - Meiriele Cruz (2020)
This research addressed the Youth and Adult Education at the Federal University of Minas Gerais (UFMG). It aimed to understand the establishment, consolidation, and continuity of operation of the Youth and Adult Elementary School Project – second segment (PROEF-2) of the Pedagogical Center of the Federal University of Minas Gerais, from 1986 to 2016. This period was chosen because 1986 marks the date of approval and beginning of the activities of PROEF-2, known as the Adult Education Project of the Pedagogical Center of UFMG at that time; and 2016 is not only the year in which the project celebrated its 30th anniversary, but it is also an institutionally important year for youth and adult education at the university, with the approval of another youth and adult education project, at the high school level, at the Pedagogical Center. Accordingly, it has become imperative to historically establish the operation pathway of PROEF-2 in dialogue with the historical process in which it has developed. Therefore, it was necessary to gather, produce and analyze a set of sources about the history of this project, projects, and activity reports stored in the Project collection and personal reports of teachers who worked on it, the production of oral testimonies, among other sources. These memory records of the Project, when composing the documentary corpus of the research, were analyzed based on a bibliography related to youth and adult education and the history of education. The results showed that the establishment of this Project was triggered by different factors, such as the existence, at the university, of employees with incomplete schooling; the need for teacher training and development of research in the area of youth and adult education; as well as the action of professors interested in the university intervention in this matter. However, its consolidation and maintenance process occurred due to a combination of factors, including the recognition of its social relevance; the structuring of the Youth and Adult Basic Education Program of the Federal University of Minas Gerais, of which the Project is an integral part; the progressive incorporation of the Project by the institution responsible for its execution, the Pedagogical Center – Elementary School of UFMG; the structuring of an internal teacher training program, especially Youth and Adult Education teachers; and the contribution to researching adult education. Also, the results show that, during its operation, the Project has accumulated experience in youth and adult education and, at the same time, accompanied and contributed to the structuring of this field of study inside and outside the Federal University of Minas Gerais. Factors that contribute to its continuity and may help in conducting investigations about the specificities and contours of Youth and Adult Education in our country.